2008
DOI: 10.1021/ja8029398
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biosynthesis of Antiprotealide and Other Unnatural Salinosporamide Proteasome Inhibitors

Abstract: A new shunt in the phenylalanine biosynthetic pathway to the nonproteinogenic amino acid L-3-cyclohex-2'-enylalanine was exploited in the marine bacterium Salinispora tropica by mutagenesis to allow for the genetic engineering of unnatural derivatives of the potent proteasome inhibitor salinosporamide A (2) such as antiprotealide (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2
17

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 21 publications
4
72
2
17
Order By: Relevance
“…[21][22][23] The C-terminal domains of CinA and CinB form the terminal NRPS module of the assembly line, and the highly homologous domain set in the salinosporamide gene cluster is known to activate the nonproteinogenic amino acid b-hydroxy-2'-cyclohexenylalanine. [12,24] Because of the structural similarity of the two compounds, and because the deduced substrate specificity code of the CinB A domain (DLMNVGGV; determined as described previously [25,26] ) showed a significant degree of similarity to that of the SalB A domain (DLLSNGGV), we propose elongation of the cinnabaramide intermediate by extension with b-hydroxy-2'-cyclohexenylalanine (Scheme 2 B). The resulting PCP-tethered cinnabaramide intermediate is then thought to undergo an intramolecular condensation promoted by the ketosynthase (CinC) to generate the g-lactam ring, which provides the CinB-bound alcohol substrate that gives rise to the offloaded b-lactone product.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…[21][22][23] The C-terminal domains of CinA and CinB form the terminal NRPS module of the assembly line, and the highly homologous domain set in the salinosporamide gene cluster is known to activate the nonproteinogenic amino acid b-hydroxy-2'-cyclohexenylalanine. [12,24] Because of the structural similarity of the two compounds, and because the deduced substrate specificity code of the CinB A domain (DLMNVGGV; determined as described previously [25,26] ) showed a significant degree of similarity to that of the SalB A domain (DLLSNGGV), we propose elongation of the cinnabaramide intermediate by extension with b-hydroxy-2'-cyclohexenylalanine (Scheme 2 B). The resulting PCP-tethered cinnabaramide intermediate is then thought to undergo an intramolecular condensation promoted by the ketosynthase (CinC) to generate the g-lactam ring, which provides the CinB-bound alcohol substrate that gives rise to the offloaded b-lactone product.…”
Section: Resultsmentioning
confidence: 87%
“…Similar enzymes have also been described in the salinosporamide biosynthesis pathway-it was suggested that these were involved in cyclohexenyl-alanine building block formation-and inactivation of a prephenate dehydratase homologue gene (salX) in the sal cluster led to the elimination of all natural salinosporamides. [12,27] It has been reported that the salinosporamide biosynthetic enzymes responsible for the activation and incorporation of the native sal-specific amino acid exhibit relaxed substrate specificities towards a number of aliphatic amino acids. [28] In that work, Moore and co-workers used a comprehensive approach that combined chemical synthesis with metabolic engineering to generate a series of salinosporamide analogues with altered bioactivities against human cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[78] Die Löschung von salX hob die Biosynthese aller Salinosporamide auf und ermöglichte die gerichtete mutagenetische Produktion einer Serie nichtnatürlicher Salinosporamid-Derivate (siehe Abschnitt 6.2). [79,80] Die anscheinend fehlenden Enzyme (also diejenigen, die an der Bildung von 44 aus 43 beteiligt sind) sowie die beiden fehlenden Reduktasen wurden noch nicht identifiziert und könnten sich außerhalb des sal-Lokus befinden. Die Hydroxygruppe an der Seitenkette wird schließ-lich durch die P450-Hydroxylase SalD eingeführt, wie durch Inaktivierung des entsprechenden Gens und der daraus resultierenden Produktion von Salinosporamid J (30) nachgewiesen wurde; diese Oxidation findet, wie sich aufgrund anderer, biochemisch charakterisierter P450-Enzyme vermuten lässt, [79] wahrscheinlich statt, während die Aminosäure 39 an die PCP-Domäne von SalB gebunden ist.…”
Section: Angewandte Chemieunclassified